2021
DOI: 10.7717/peerj.12612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of evolutionary relationships and DNA markers in the medicinally important genus Fritillaria based on chloroplast genomics

Abstract: The genus Fritillaria has attracted great attention because of its medicinal and ornamental values. At least three reasons, including the accurate discrimination between various Fritillaria species, protection and sustainable development of rare Fritillaria resources as well as understanding of relationship of some perplexing species, have prompted phylogenetic analyses and development of molecular markers for Fritillaria species. Here we determined the complete chloroplast (CP) genomes for F. unibracteata, F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
2
4
0
2
Order By: Relevance
“…Phylogenomic analysis supported the monophyly of the subgenus Fritillaria. More importantly, 23 species in the subgenus could be divided into four major clades (Clade I, II, III, and IV) with high support values (Figure 4), in accordance with the previous findings based on chloroplast regions and ITS (Day et al, 2014;Huang et al, 2018;Zhang et al, 2021). The four clades possessed obvious geographic structure except the last one (Figures 4, 7).…”
Section: Phylogenetic Relationships and Divergence Time Of Fritillari...supporting
confidence: 88%
See 2 more Smart Citations
“…Phylogenomic analysis supported the monophyly of the subgenus Fritillaria. More importantly, 23 species in the subgenus could be divided into four major clades (Clade I, II, III, and IV) with high support values (Figure 4), in accordance with the previous findings based on chloroplast regions and ITS (Day et al, 2014;Huang et al, 2018;Zhang et al, 2021). The four clades possessed obvious geographic structure except the last one (Figures 4, 7).…”
Section: Phylogenetic Relationships and Divergence Time Of Fritillari...supporting
confidence: 88%
“…Among them, the first clade, distributed in southwest China, was undoubtedly the most complicated group probably due to its recent diversification. This work provided a comprehensive topological structure for the Fritillaria in China although the previous studies have revealed similar results based on limited samples and DNA markers (Park et al, 2017;Bi et al, 2018;Huang et al, 2018;Li et al, 2018;Zhang et al, 2021). Moreover, it is worth noting that of the suspicious species, "F. omeiensis" was not clustered into the same clade with F. crassicaulis, which was treated as a synonym for the latter in Flora of China (2000); similarly, "F. hupehensis" was also far from the F. monantha (Figure 4).…”
Section: Phylogenetic Relationships and Divergence Time Of Fritillari...supporting
confidence: 55%
See 1 more Smart Citation
“…Bununla birlikte, Zhang ve diğ [44]. yapmış olduğu araştırmada Fritillaria türlerinde tüm kloroplast (CP) genomlarını belirleyerek elde edilen ycf1, trnL, trnF, ndhD, trnN-trnR, trnE-trnT, trnN, psbM-trnD, atpI ve rps19 moleküler markırlarının taksonomik çalışmalarda yararlı olacağını rapor etmişlerdir[44].Zambakgiller ailesine ait Fritillaria cinsinin bir türü olan Aygül lalesinin bilimsel adı "Fritillaria eduardii"-Eduard çiçeğidir.…”
unclassified
“…Bununla birlikte, Zhang ve diğ [44]. yapmış olduğu araştırmada Fritillaria türlerinde tüm kloroplast (CP) genomlarını belirleyerek elde edilen ycf1, trnL, trnF, ndhD, trnN-trnR, trnE-trnT, trnN, psbM-trnD, atpI ve rps19 moleküler markırlarının taksonomik çalışmalarda yararlı olacağını rapor etmişlerdir[44].Zambakgiller ailesine ait Fritillaria cinsinin bir türü olan Aygül lalesinin bilimsel adı "Fritillaria eduardii"-Eduard çiçeğidir. F. eduardii; karbonat içeren topraklarda, nemli, kireç ve taşlı toprağa sahip olan orman bölgelerinde, çalıların arasında, ağaçların altında, bazen çalıların ve ağaçların bulunmadığı açık alanlarda, dağların genelde batı ve kuzey kısımlarında deniz seviyesinden 700-2500 metre yükseklikte Eduard Regel tarafından bahsedilen kokususuz Fritillaria bitkilerinin de F. eduardii'nin biri Fritillaria eduardii var.…”
unclassified